Subsıstence (Food) of Erzurum Castle in 18th Century, And The Regıons Where Supplıed - Demlikoğlu, Uğur (Fırat University, 2018)
Erzurum is on one of the most important routes of the historical Silk Road connecting Anatolia to Iran and the Caucasus due to its strategic location. Erzurum is an important region, not only about trade, but also in terms of military and logistic. Erzurum, annexed the Ottoman State during the reign of Yavuz Sultan Selim (Sultan Selim The Stern), has a logistical base status in all military expeditions to be made on Iran, Caucasia and Baghdad. This situation continued in the 18th century. Erzurum Castle became the assembly center of the Ottoman army in 18th century, during the war between the Ottoman Empire and the Safavids. The supply and transportation of the subsistence needed by the Ottoman army, located at Erzurum Castle, requires an important organization.. In this article, in the light of the present documents, the subsistence of Ottoman Army, located in Erzurum Castle, the expenses made for the subsistence, the regions where the subsistence was supplied and their transportation to Erzurum Castle were discussed.

Erzurum, stratejik konumu itibariyle Anadolu’yu İran ve Kafkasya’ya bağlayan tarihi İpek yolunun en önemli güzergâhlarının birinde yer almaktadır. Erzurum sadece ticarette değil aynı zamanda askeri ve lojistik bakımından da önemli bir bölgedir.  Yavuz Sultan Selim döneminde Osmanlı Devletine katılan Erzurum; İran, Kafkasya ve Bağdat üzerine yapılacak tüm askeri seferlerde lojistik bir üst durumundadır. Bu durum 18. yüzyılda da devam etmiştir. Erzurum Kalesi, 18. yüzyılda Osmanlı Devleti ile Safeviler arasında yapılan savaşlarda Osmanlı ordusunun toplanma merkezi haline gelmiştir. Erzurum Kalesi’nde bulunan Osmanlı ordusunun ihtiyaç duyduğu iaşenin temin edilmesi ve nakliyesi önemli bir organizasyonu gerektirmektedir. Bu makalede; mevcut belgelerin ışığında Erzurum Kalesi’nde bulunan Osmanlı ordusunun iaşesini, iaşeye yapılan masrafları, iaşenin temin edildiği bölgeler ile Erzurum Kalesi’ne nakliyesi ele alınmıştır.
18. YÜZYILDA ERZURUM KALESİ’NİN İAŞESİ VE TEMİN EDİLDİĞİ BÖLGELER